2006
DOI: 10.4028/www.scientific.net/msf.514-516.8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organic Hole Transport Layers for Molecular Electronic Systems

Abstract: Five novel triarylamines based on the bulky dehydroabietic acid unit have been synthesised, and their potential as hole transport layers tested. This bulky group facilitates film preparation and stability without significantly affecting the chemical or materials properties. Three of these systems present excellent stability, and show considerable potential for device applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…[7,8] We have recently shown the advantages of using dehydroabietic acid based amines in terms of their solution processibility, charge transport and film stability. [9,10] Herein, we report the synthesis and the photophysical properties of six new dehydroabietic acid based amine end-capped derivatives of two p-phenylenevinylene trimers (MBOPV3 and EHOPV3).…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] We have recently shown the advantages of using dehydroabietic acid based amines in terms of their solution processibility, charge transport and film stability. [9,10] Herein, we report the synthesis and the photophysical properties of six new dehydroabietic acid based amine end-capped derivatives of two p-phenylenevinylene trimers (MBOPV3 and EHOPV3).…”
Section: Introductionmentioning
confidence: 99%
“…However, these require both high solubility in volatile solvents and compounds which do not crystallise readily. We have recently shown that triarylamines with a resin acid moiety have excellent solubility and film-forming properties which make them good candidates as hole transport layers [7,8]. We extend this study to dehydroabietic acid-based triarylaminequinoxaline bipolar compounds with potential for device applications.…”
Section: Introductionmentioning
confidence: 82%
“…They have been synthesized following a two-step procedure as depicted for (1-4) in Scheme 1. Thus, by a mild acid catalyzed condensation of two ortho-anilines, respectively, methyl 13,14-diaminodeisopropyldehydroabietate [10] or commercially available 1,2-diaminobenzene with dibromobenzil, the dibromoquinoxaline intermediates were prepared, which by reaction with different diarylamines gave the compounds (1-4) and (5)(6)(7)(8). The amination reaction takes place rapidly by using the catalyst combination of Pd(OAc) 2 and a bulky and electron-rich phosphine, P(t-Bu) 3 [11].…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent these problems, many efforts have been devoted to the synthesis of new HTL materials with better thermal and morphological stability, and there is strong interest in the development of amorphous molecular materials for these applications. 1 We have previously shown that triarylamines containing a bulky aryl-substituent (a dehydroabietic acid methyl ester moiety) 9,10 inhibit crystallisation and show good solubility characteristics. In addition, we have also indicated the potential of dehydroabietic acid based bipolar arylamine-quinoxalines for device applications.…”
Section: Introductionmentioning
confidence: 99%